Neuroimaging in Autoimmune and Neuroinflammation-Related Epilepsies - Saleem, Sheena; Altinok, Deniz; Kumar, Ajay (Journal of Pediatric Epilepsy, 2018)
Autoimmune encephalitis is increasingly recognized as a cause of new onset altered mental status and seizures with a wide range of neuroimaging findings. We will describe the neuroimaging findings in autoimmune and neuroinflammation-related epilepsies.
Keywords: autoimmune; neuroinflammation; neuroimaging